THE INFLUENCE OF ACCOUNTABILITY ON CLEAN-CORRUPTION PERCEPTION IN LOCAL GOVERNMENT - Ahmad Nur Ikhwan; Bambang Subroto; Abdul Ghofar (Universitas PGRI Madiun, 2016)
This study aimed to analyze and examine the influence of financial accountability, performance accountability and public services accountability on the clean-corruption perception. The study population was the local government in Indonesia. Sampling technique used is purposive sampling and obtained 104 sample. The approach used in this research is a quantitative with an analysis tool used is multiple regression. The results show financial accountability and public services accountability influencing the clean-corruption perception, whereas performance accountability can’t influencing the clean-corruption perception. Hence it can be concluded that by improving the financial accountability and public services accountability can reduce the prevalence of corruption at the local government.